Experimental performance evaluation of solar still with zig-zag shape air cooled condenser: An energy–exergy analysis approach - Dinesh Mevada; Hitesh Panchal; Anand Nayyar; Kamal Sharma; A. Muthu Manokar; Mahmoud S. El-Sebaey; Abdelazim G. Hussien (Energy Reports, 2023)
In the present experimental effort is made to increase the performance of a solar still (SS) by including a novel design of a zig-zag-shaped air-cooled condenser (ZZACC) and cuprous oxide (CuO) as a nanomaterial. Research work is conducted in the climatic conditions of Gandhinagar, Gujarat, India, from September to November 2020. A comparison was made to assess the performance of a conventional solar still (CSS) and a solar still equipped with a zig-zag shape air-cooled condenser (SSWZZACC) with CuO. The experiments’ findings showed that adding CuO to SSWZZACC increases the distillate production by 46.83% and the daily energy efficiency by 45.98%, respectively, compared to CSS. Also, SSWZZACC demonstrates a better efficiency of exergy and latent heat of vaporization than CSS because CuO causes an increase in the evaporative heat transfer coefficient of water. In life cycle cost analysis study discovered that SSWZZACC has a 27.77% lower cost per litre of water (CPL) than CSS. The obtained maximum energy and exergy efficiency values for CSS and SSWZZACC were 2.36% & 25.75% and 3.9% & 37.59%, respectively. In economic and environmental aspects, it was found that SSWZZACC with CuO showed a cost-effective desalination unit and was highly effective from a carbon credit point of view (CCP) by CO2 mitigation.